Review of Nexosa Diakonoff in Vietnam, with a new species and a new subspecies, and transfer to the tribe Archipini (Lepidoptera: Tortricidae: Tortricinae: Archipini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2015)
The species of Nexosa Diakonoff, 1977 in Vietnam are reviewed: Nexosa hexaphala (Meyrick); Nexosa hexaphala tamdaoana Heppner & Bae, n. subsp.; and Nexosa tonkinensis Heppner & Bae, n. sp. The genus is transferred to the tribe Archipini (Tortricidae: Tortricinae).